A systematic review of the connection between serum uric acid levels and the risk of cardiovascular disease - Wang, Jin-jin; Yi, Jin-ke; Zhou, Li-rong; Chen, Jun; Zhang, Bin-qiang; Huang, Hui-min; Wei, Ying (Frontiers in Cardiovascular Medicine, 2025)
Serum uric acid (SUA) has emerged as a significant biomarker for cardiovascular disease (CVD) risk assessment, garnering increasing attention in recent years. As CVD remains a leading cause of global mortality, identifying effective biomarkers for risk stratification is of paramount importance. Current evidence indicates a strong association between elevated SUA levels and increased CVD risk. However, the precise mechanisms and confounding factors underlying this relationship remain unclear. This review examines the link between SUA and CVD, exploring potential biological pathways—including metabolic syndrome, inflammatory responses, and oxidative stress—that may mediate this association. By synthesizing existing literature, this article aims to provide insights for future research and clinical applications, ultimately enhancing the understanding of SUA's utility in CVD risk evaluation.